Pengaruh Kepemimpinan Kepala Sekolah, Mutu Guru, Proses Pembelajaran, dan Penggunaan Media Pembelajaran terhadap Mutu Sekolah Menengah Pertama (SMP) di Kecamatan Semau Selatan Kabupaten Kupang - Feriderieks Holeng; Yulius Yasinto; Cozmas Fernandez; Simon Sia Niha; Henny A. Manafe (Dinasti Review, 2022)
Abstract: Referring to the results of the study of documents and interviews, it was found that the quality of SMP Negeri 1 Semau Selatan and SMP Negeri 2 Semau Selatan One Roof was still low. It is suspected that the low quality of these two SMPs is influenced by the leadership of the principal, the quality of the teachers, the learning process, and the use of learning media. This study was carried out in two junior high schools in Semau Selatan District with a population of 32 teachers at the two junior high schools. The population in this study has small number so all members of the population are taken as a sample (census). Data were collected through questionnaires and then analyzed using descriptive statistics and inferential statistics (multiple linear regression). The results of the descriptive statistical analysis show that the quality of the school is in a good category (73.85%), the leadership of the principal is good (76.13%), the quality of the teachers is good (76.81%), the learning process is good (73.85%), and the use of good learning media (75.47%). The results of the t-test show if principal leadership (2.269, sig 0.031<0.05), teacher quality (7.701, sig 0.000<0.05), learning process (3.641, sig 0.001<0.05), and use of learning media (3.100, sig 0.004<0.05) has a positive or significant impact on school quality. The results of the F test showed that the four independent variables (5.361, sig 0.000 <0.05) have a positive or significant impact on school quality. The results of the coefficient of determination show that the four independent variables contribute 89.6% to school quality and the remaining 10.4% is obtained through other variables not listed in this study. Abstrak: Merujuk pada hasil studi dokumen dan wawancara ditemukan bahwa mutu SMP Negeri 1 Semau Selatan dan SMP Negeri 2 Semau Selatan Satu Atap masih rendah. Diduga bahwa rendahnya mutu dua SMP ini dipengaruhi oleh kepemimpinan kepala sekolah, mutu guru, proses pembelajaran maupun penggunaan media pembelajaran. Kajian ini terlaksana di dua SMP di Kecamatan Semau Selatan dengan populasinya adalah 32 orang guru pada dua SMP tersebut. Populasi pada kajian ini memiliki jumlah yang kecil sehingga semua anggota populasi diambil sebagai sampel (sensus). Data dikumpulkan melalui kuesioner kemudian dianalisis mempergunakan statistik deskriptif maupun statistik inferensial (regresi linear berganda). Hasil analisis statistik deskriptif memperliahtkan bila mutu sekolah berkategori baik (73,85%), kepemimpinan kepala sekolah baik (76,13%), mutu guru baik (76,81 %), proses pembelajaran baik (73,85%), dan penggunaan media pembelajaran baik (75,47%). Hasil Uji t memperliahtkan bila: kepemimpinan kepala sekolah (2,269, sig 0,031<0,05), mutu guru (7,701, sig 0,000<0,05), proses pembelajaran (3,641, sig 0,001<0,05), dan penggunaan media pembelajaran (3,100, sig 0,004<0,05) memengaruhi positif maupun signifikan bagi mutu sekolah. Hasil uji F memperlihatkan bila empat variabel independen (5,361, sig 0,000<0,05) memengaruhi positif maupun signifikan bagi kualitas sekolah. Hasil koefisien determinasi memperlihatkan bila empat variabel independen menyumbang 89,6% pada mutu sekolah dan sisanya 10,4% diperoleh melalui variabel lainnya yang tidak tertera pada kajian ini.